THE INTERPLAY BETWEEN LEARNING MEDIA, MOTIVATION AND LEARNING OUTCOMES: INSIGHTS FROM INDONESIAN EFL CONTEXT - Iswadi Iswadi (Universitas Indraprasta PGRI, 2021)
The objectives of the study are to explore the impact of English comic learning media towards English’s learning outcomes, the impact of learning motivation towards English’s learning outcomes, and the interaction effect between English comic learning media and learning motivation towards English’s learning outcomes. The method of research is experimental with 2x2 factorial design. Data collection techniques are multiple choice and questionnaires. Population of the study are 175 students. Sample of the study are 60 students. Random sampling are used for gaining sample. The researcher used SPSS 22.0 version to analyze data. The conclusions of this study are: (1) There is a significant impact of English comic learning media towards English’s learning outcomes because significant value is 0.000 < 0.05.(2) There is a significant impact of learning motivation towards English’s learning outcomes because significant value is 0.000 < 0.05. (3) There is a significant interaction impact between English comic learning media and learning motivation towards English’s learning outcomes because significant value is 0.004 < 0.05.